Systematic validation of experimental data usable for verifying the multiaxial fatigue prediction methods - J. Papuga; S. Parma; M. Ruzicka (Fracture and Structural Integrity)
The paper discusses some of the issues, the researchers interested in verifying various multiaxial fatigue limit estimation solutions are facing to. Even recently, newly proposed criteria have been or are tested on dozens of experimental inputs. Papuga in [1] pointed out, that applicability of the most often used test batch is limited and only half of these data items is worth using for such purposes. This paper extends that analysis by describing the weak points of various data sets used in this domain for validating new proposals on multiaxial fatigue limit estimates. The conclusion from the extensive analysis is that the researchers should adopt other test sets only if they very well know their background.